(untitled) (Neo Scientific Peer Reviewed Journal, 2024)
This article examines the issue of the role of fairy tales in the process of learning Russian as a foreign language. The study confirms the effectiveness of using fairy tales in educational contexts as they enable students to develop linguistic and cultural competence. Through the analysis of the motives presented in fairy tales, students can immerse themselves more deeply in Russian culture and understand the mentality of the native language nation.